1980
DOI: 10.1094/phyto-70-1158
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxygen, Carbon Dioxide, and Ethylene on Growth, Sclerotial Production, Germination, and Infection bySclerotinia minor

Abstract: , for use of controlled-atmosphere facilities; to K. A. Kimble and Curt Waters for technical assistance; and to Jeff Hall for preparation of illustrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…However, a preliminan experiment was inconclusive . Ethylene could also be involved, as shown by Imolehin & Grogan (1980) with the root pathogen Sclerotinia minor, as well as ammonia, amines, alcohols, sulphur compounds or low-molecular weight fatty acids . However, all these experiments having been done in very artificial laboratory conditions, great caution should be taken in extrapolating to the rhizosphere.…”
Section: Effect Of Mhbs On the Fungal Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a preliminan experiment was inconclusive . Ethylene could also be involved, as shown by Imolehin & Grogan (1980) with the root pathogen Sclerotinia minor, as well as ammonia, amines, alcohols, sulphur compounds or low-molecular weight fatty acids . However, all these experiments having been done in very artificial laboratory conditions, great caution should be taken in extrapolating to the rhizosphere.…”
Section: Effect Of Mhbs On the Fungal Growthmentioning
confidence: 99%
“…Attempts to identify these volatile substances are presently underway. Carbon dioxide could play a role, because it has been shown that, depending on its concentration, it differentially inhibits or stimulates the growth of different fungi (Boasson & Shaw^ 1979Le Tacon, Skinner & Mosse, 1983;Straatsma, Van Griensven & Bruinsma, 1986;Imolehin & Grogan, 1980). However, a preliminan experiment was inconclusive .…”
Section: Effect Of Mhbs On the Fungal Growthmentioning
confidence: 99%
“…Under furrow irrigation, however, nearly the entire host biomass (both above-and belowground) was converted to pathogen biomass, suggesting the soilborne inoculum under this management practice could increase rapidly with repeated lettuce crops, as in the Salinas Valley. Previously, the production of sclerotia on belowground plant parts was reported either as not occurring (8) or as occurring only down to 5 cm below the surface of the soil (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…A number of factors affect the survival and germination of fungal sclerotia such as soil moisture and temperature (Duniway, et al, 1977;Huang, 1980;Hannusch, andBoland, 1996 Mclaren, et al, 1996) sclorotial shape (Huang and Kozub, 1994), soil gases (Imolehin and Grogan, 1980) chemicals such as cinnamic acid derivatives (Galal and El-Bana, 2002), activities of other microorganisms (Mischke, et. al., 1995 andBell, et.…”
Section: Effect Of Ca-salts On the Carpogenic Germination Of S Sclero...mentioning
confidence: 99%